Subtle Interactions and Electron Transfer between UIII, NpIII, or PuIII and Uranyl Mediated by the Oxo Group. Issue 41 (15th September 2016) - Arnold, Polly L.; Dutkiewicz, Michał S.; Zegke, Markus; Walter, Olaf; Apostolidis, Christos; Hollis, Emmalina; Pécharman, Anne‐Fréderique; Magnani, Nicola; Griveau, Jean‐Christophe; Colineau, Eric; Caciuffo, Roberto; Zhang, Xiaobin; et al.
Abstract: A dramatic difference in the ability of the reducing An III center in AnCp3 (An=U, Np, Pu; Cp=C5 H5 ) to oxo‐bind and reduce the uranyl(VI) dication in the complex [(UO2 )(THF)(H2 L)] (L="Pacman" Schiff‐base polypyrrolic macrocycle), is found and explained. These are the first selective functionalizations of the uranyl oxo by another actinide cation. At‐first contradictory electronic structural data are explained by combining theory and experiment. Complete one‐electron transfer from Cp3 U forms the U IV ‐uranyl(V) compound that behaves as a U V ‐localized single molecule magnet below 4 K. The extent of reduction by the Cp3 Np group upon oxo‐coordination is much less, with a Np III ‐uranyl(VI) dative bond assigned. Solution NMR and NIR spectroscopy suggest Np IV U V but single‐crystal X‐ray diffraction and SQUID magnetometry suggest a Np III ‐U VI assignment. DFT‐calculated Hirshfeld charge and spin density analyses suggest half an electron has transferred, and these explain the strongly shifted NMR spectra by spin density contributions at the hydrogen nuclei. The Pu III –U VI interaction is too weak to be observed in THF solvent, in agreement with calculated predictions. Abstract : TRU to U : A dramatic difference in the ability of the reducing An III center in AnCp3 (An=U, Np, Pu; Cp=C5 H5 ) to oxo‐bind and reduce the uranyl(VI) dication in the complex [(UO2 )(THF)(H2 L)] (L="Pacman" Schiff‐base polypyrrolic macrocycle), is found and explained. These are the first selective functionalizations of the uranyl oxo by another actinide cation. At‐first contradictory electronic structural data are explained by combining theory and experiment.